Genetic Background of Kirgiz Ethnic Group From Northwest China Revealed by Mitochondrial DNA Control Region Sequences on Massively Parallel Sequencing - Wang, Hongdan; Chen, Man; Chen, Chong; Fang, Yating; Cui, Wei; Lei, Fanzhang; Zhu, Bofeng (Frontiers in Genetics, 2022)
The mitochondrial DNA (mtDNA) has been used to trace population evolution and apply to forensic identification due to the characteristics including lack of recombination, higher copy number and matrilineal inheritance comparing to nuclear genome DNA. In this study, mtDNA control region sequences of 91 Kirgiz individuals from the Northwest region of China were sequenced to identify genetic polymorphisms and gain insight into the genetic background of the Kirgiz ethnic group. MtDNA control region sequences of Kirgiz individuals presented relatively high genetic polymorphisms. The 1122 bp sequences of mtDNA control region could differ among unrelated Kirgiz individuals, which suggested a good maternal pedigree tracing capability among different Kirgiz individuals. The neutrality test, mismatch distribution, Bayesian phylogenetic inference, Bayesian skyline analysis, and the median network analyses showed that the Kirgiz group might occurred population expansion, and the expansion could be observed at about ~53.41 kilo years ago (kya) when ancestries of modern humans began to thrive in Eurasia. The pairwise population comparisons, principal component analyses, and median network analyses were performed based on haplogroup frequencies or mtDNA control region sequences of 5886 individuals from the Kirgiz group and other 48 reference populations all over the world. And the most homologous haplotypes were found between Kirgiz individuals and the East Asian individuals, which indicated that the Kirgiz group might have high frequencies of gene exchanges with the East Asian populations.